Character Development Strategy for Tolerance in Islamic Boarding Schools - Muid, Abdul; Shohib, Muhammad; Askarullah, Anas (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study aims to describe the character of tolerance and its development strategy at Mathlabul Ulum Jambu Lenteng Islamic Boarding School Sumenep. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the character of tolerance at Mathlabul Ulum Islamic Boarding School was developed through four forms, namely planting tolerance values, learning tolerance values, acculturation of tolerance, and Niha'i program. The cultivation of tolerance values has been the core strategy of the pesantren since its inception, which is motivated by the historical reality of the surrounding community, which is full of conflict and disharmony. The learning of tolerance values is integrated into the formal curriculum and the teaching of moral books. Acculturation of tolerance is done through activities that involve interaction with the community, such as gotong royong, night patrols, imamah prayers, and routine recitations. The Niha'i program, which consists of Real Work Lectures (KKN) and community service, is the culmination of tolerance character development. The strategy of developing a tolerance character is carried out through exemplary kai/caregiver, fostering tolerance values, and community service. The findings of this study confirm and strengthen the urgency of tolerance education in pesantren, as well as contribute a new perspective on a comprehensive and systematic model of tolerance character development.